DINAMIKA PROSES COLLABORATIVE GOVERNANCE DALAM PENINGKATAN KUALITAS PENDIDIKAN DI KABUPATEN BOGOR - Azmi Istihsan Majid; Rahman Mulyawan; Rudiana (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
Improving the quality of education in Bogor Regency faces multidimensional problems as reflected in the average length of school of 8.72 years, the number of school dropouts of 13,186 children, and the Community Literacy Development Index of 9.50 in 2025. This condition shows the need for the involvement of various stakeholders in the implementation of education. This study aims to analyze the dynamics of the collaborative governance process in improving the quality of education in Bogor Regency based on the five dimensions of the collaborative process of Ansell and Gash (2007), namely face-to-face dialogue, trust building, commitment to the process, shared understanding, and intermediate outcomes. The research uses a descriptive qualitative approach through interviews, observations, and documentation of eight informants from elements of local government, DPRD, PGRI, education units, the private sector, and the community. The results of the study show that collaboration has been formed through various communication forums and educational programs, but it has developed in an inuniform manner. Dialogue between actors still tends to be formal, trust and commitment are not stable, and understanding of the root causes of education problems has not been fully divided. The achievement of collaboration has resulted in small wins, but it is still partial and uneven. These findings suggest that the existence of forums and multi-stakeholder engagement has not automatically resulted in substantive collaboration; The quality of interaction, trust, commitment, and mutual understanding are important factors in the sustainability of educational collaboration.